Development of a dynamic wind tunnel rig for aircraft pure pitching motion - Mansor, Shuhaimi (Faculty of Mechanical Engineering, 2000)
This paper presents the design, fabrication and testing of a dynamic wind tunnel test rig that is used in conjunction with aircraft dynamics theory in estimating aerodynamics stability derivatives. The value of and can be obtained from free oscillation theory of pure pitching motion. The rig comprises a scale down 1:30 full model of two-seater light aircraft, accelerometer, charge amplifier, A/D converter and IBM-PC. The result of the study has shown that the test rig is capable of predicting the derivatives. The effect of Reynold?s number to the dynamics testing can be considered small as in dynamic testing, where the rate of change was measured rather than the absolute value. Finally, the rig can be used as part of the experimental testing in flight dynamics for aircraft design.